DELTA-sigma phase interpolation direct digital frequency synthesizer - O. I. Polikarovskykh (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
We consider the delta sigma direct computer synthesizer direct synthesis of phase interpolation. The phase interpolation is performed using a single capacitor integrator and digital-to-analog converters. Delta-sigma conversion of distinguished ability provides high frequency and low noise quantization the output direct digital frequency synthesizer. Simulated operation of the synthesizer, confirmed the high quality features of the synthesized signals.